Peningkatan Minat Belajar Siswa Kelas 4 UPTD SDN LABANG Pada Pembelajaran IPA Denngan Menggunakan Model Pembelajaran Outdoor Learning (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2024)
This research was motivated by the lack of interest in learning for 4th grade students of UPTD SDN Labang in science learning. This research method is Classroom Action Research (CAR) which is carried out in two cycles. The research subjects were students of class IV UPTD SDN Labang with a total of 20 students, consisting of 8 male students and 12 female students. Data collection techniques used are observation, interviews and questionnaires. The research instruments in this study were interview guidelines, project assessment sheets, observation sheets, and questionnaire sheets. The data analysis technique used is descriptive qualitative. In the first cycle, which was conducted with interviews and questionnaires, problems were found, namely the lack of interest in learning for fourth grade students in ecosystem material caused by several factors, including the teacher-centered learning process, the use of unattractive media, and lack of motivation to learn. In the second cycle is the implementation of improvements to overcome the problems and obstacles identified. Consists of stages, namely the stages of planning, implementation, observation, and reflection. After improvements were made in cycle II, students were more enthusiastic when participating in science learning by using interesting media and Out Door Learning learning models. From this it can be concluded that the use of interesting media and models can increase the learning interest of fourth grade students of UPTD SDN Labang.